2009
DOI: 10.1243/09544070jauto1083
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a multiple injection strategy on the development of high-pressure diesel sprays

Abstract: Computational fluid dynamics results are presented providing information on the influence of multiple injection strategy on fuel vaporization characteristics under conditions typical of direct injection, turbocharged, high-speed automotive diesel engines. The fuel is assumed to be injected from a high-pressure common rail injector nozzle. Focus is given on the number of multiple injections and dwell-time on the evaporating spray plume development. Comparison between the different cases is performed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…It has long been recognized that the details of internal nozzle flow have a strong impact on the spray and its atomization characteristics [1,2]. This is particularly true when cavitation occurs within the nozzle passage.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been recognized that the details of internal nozzle flow have a strong impact on the spray and its atomization characteristics [1,2]. This is particularly true when cavitation occurs within the nozzle passage.…”
Section: Introductionmentioning
confidence: 99%
“…Here φ c , ρ c , V c , p are the volume fraction, the density, the velocity, and the pressure of the continuous phase, Q mass d is the source term, n d and M d are the dispersed phase particle concentration and mass, τ eff is the effective viscous stress tensor, which depends on the continuous phase dynamic coefficient of molecular and turbulent viscosities. Turbulence is described using the KEFV model [3,5,[20][21][22][23]. The dispersed phase influences the carrier phase through the terms on the right-hand side of the Navier-Stokes equations describing the motion of the carrier phase (coolant gas).…”
Section: Continuous Phasementioning
confidence: 99%
“…In [14], calculations were carried out for chambers Three-dimensional Numerical Model of Kerosene Evaporation in Gas Turbine Combustors of various working volumes; it is noted that the simulation results show a good agreement with experimental data. Works by S. Tonini et al [21,22] are also devoted to modeling the spraying of dense diesel fuel compressed to high pressure -in [21] a description of the model, the approaches used, validation of the model is presented, and in [22] the influence of the number of fuel injections and the time between injections on the development of a cloud of droplets in the working chamber is studied. Several papers [18,19] are devoted to the study of the flow parameters inside the nozzle influence on the fuel atomization in the working chamber.…”
Section: Introductionmentioning
confidence: 99%
“…From the published literature, it is observed that the choice of models ranges from simple thermodynamic models 22 to complex multidimensional computational fluid dynamics (CFD) modelling. 23 The CFD models provide more detailed spatial variation at the expense of the computational time compared with phenomenological models.…”
Section: Introductionmentioning
confidence: 99%